Violence against women in Melanesia and East Timor : building on global and regional promising approaches - Australian Agency for International Development. Office of Development Effectiveness (Canberra : AusAID Office of Development Effectiveness, 2008)
The Office of Development Effectiveness has undertaken a study to assess the effectiveness of methods currently being used to address violence against women and girls in five of Australia's neighbouring countries: Fiji, Papua New Guinea, Solomon Islands, Vanuatu and East Timor. The result is a package of reports that outlines the perspectives and hopes of a broad spectrum of Melanesian and East Timorese society. The study used a participatory approach to gather input from over 700 individuals from government and civil society. The effectiveness of local and international approaches was assessed using this approach and the result is a framework for action that seeks to reduce the incidence of violence against women and improve support services. The three key areas identified in the framework are: increasing women's access to justice; increasing women's access to support services; and, preventing violence.
Executive summary -- 1. Background to the report -- 2. A framework for understanding violence against women and girls -- 3. What is known about violence against women in Melanesia and East Timor? -- 4. An integrated approach to addressing violence against women -- 5. Improving women's access to justice -- 6. Support for services -- 7. Prevention of violence -- 8. Conclusions and recommendations.
Bibliography: p. 94-100.
Also available in an electronic version via the Internet. Address as at 23 Dec. 2008: http://www.ode.ausaid.gov.au/news/news08.html
Keywords: Economic assistance, Australian -- Developing countries; Women -- Crimes against -- Melanesia; Women -- Crimes against -- Timor-Leste.